2017
DOI: 10.1590/s1806-92902017000300001
|View full text |Cite
|
Sign up to set email alerts
|

Presence of roosters in an alternative egg production system aiming at animal welfare

Abstract: -The objective of this study was to evaluate the effect of the presence of roosters on welfare and egg production of laying hens reared in an alternative system. Two breeding systems were established: barn 1 -laying hens reared without roosters (4500 birds); and barn 2 -laying hens reared with roosters (4500 layers and 250 roosters). In the poultry facilities, microclimate, egg production, mortality rate, and bird behavior were evaluated. Microclimate analysis showed that the birds were subjected to periods of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(25 reference statements)
0
3
1
Order By: Relevance
“…Our results show no evidence that the roosters were beneficial in reducing feather loss in contrast to Louton et al (2017), who reported that the presence of roosters reduced the risk of feather pecking. Pereira et al (2017) observed that the presence of roosters reduced mortality and altered hen behavior, but their ratio of roosters to hens was far higher (250 roosters in a flock of 4,500 hens) than in the present study. We found that the number of roosters in the flocks was associated with a higher prevalence of feather loss on the back and dirty birds.…”
Section: Discussioncontrasting
confidence: 86%
“…Our results show no evidence that the roosters were beneficial in reducing feather loss in contrast to Louton et al (2017), who reported that the presence of roosters reduced the risk of feather pecking. Pereira et al (2017) observed that the presence of roosters reduced mortality and altered hen behavior, but their ratio of roosters to hens was far higher (250 roosters in a flock of 4,500 hens) than in the present study. We found that the number of roosters in the flocks was associated with a higher prevalence of feather loss on the back and dirty birds.…”
Section: Discussioncontrasting
confidence: 86%
“…In addition, the systems provide free dietary choice for laying hens to promote their foraging activities, thus improving animal welfare [ 145 ]. Finally, putting roosters and laying hens together reduces the incidence of fear and feather damage in laying hens, and the presence of a rooster broadens the behavioural repertoire of laying hens [ 146 ]. Notably, predation was not yet a key concern.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual courtship behavior is performed before the cover and involves wing movements and vocalizations from males to females. It is usually exhibited by the dominated males instead of heavier ones (PEREIRA et al 2017).…”
Section: Sexual Behaviormentioning
confidence: 99%